Staphylococcus aureus colonizing the skin microbiota of adults with severe atopic dermatitis exhibits genomic diversity and convergence in biofilm traits - Francesca Sivori; Ilaria Cavallo; Mauro Truglio; Flavio De Maio; Maurizio Sanguinetti; Giorgia Fabrizio; Valerio Licursi; Massimo Francalancia; Fulvia Fraticelli; Ilenia La Greca; Federica Lucantoni; Emanuela Camera; et al. (Biofilm)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder exacerbated by Staphylococcus aureus colonization. The specific factors that drive S. aureus overgrowth and persistence in AD remain poorly understood. This study analyzed skin barrier functions and microbiome diversity in lesional (LE) and non-lesional (NL) forearm sites of individuals with severe AD compared to healthy control subjects (HS). Notable differences were found in transepidermal water loss, stratum corneum hydration, and microbiome composition. Cutibacterium was more prevalent in HS, while S. aureus and S. lugdunensis were predominantly found in AD LE skin. The results highlighted that microbial balance depends on inter-species competition. Specifically, network analysis at the genus level demonstrated that overall bacterial correlations were higher in HS, indicating a more stable microbial community. Notably, network analysis at the species level revealed that S. aureus engaged in competitive interactions in NL and LE but not in HS. Whole-genome sequencing (WGS) showed considerable genetic diversity among S. aureus strains from AD. Despite this variability, the isolates exhibited convergence in key phenotypic traits such as adhesion and biofilm formation, which are crucial for microbial persistence. These common phenotypes suggest an adaptive evolution, driven by competition in the AD skin microenvironment, of S. aureus and underscoring the interplay between genetic diversity and phenotypic convergence in microbial adaptation.